CONTEMPORARY ASPECTS OF AUTOMATED VISUAL OBJECTS CREATION IN GAMIFICATION TASKS - PASTUSHENKO, DENYS; VOVK, OLENA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
This paper investigates the utilization of gamification in the creation and use of virtual objects, analyzing methodical aspects of automated visual object generation. Various analogues of automatic virtual object creation are examined, assessing their effectiveness in gamification tasks. The strengths and weaknesses of automated techniques for building virtual objects are discussed, and user feedback on “gamification principles” is collected to evaluate user satisfaction. Based on the findings, the paper concludes on the efficiency of gamification as pedagogical means and proposes implementation options for visual object design and user feedback. The developed methodology is valuable for designers and developers seeking to create engaging gaming approaches in IT. The article identifies the need for improvement in data generation and processing methods used in gamification tasks. It presents a literature review on the topic, focusing on the selection, processing, and comparison of statistical data. The available generation methods and methodical aspects of automated visual object creation in gamification tasks are explored. Analogues of automated virtual object creation are presented, evaluating their characteristic features, strengths, and weaknesses. The paper outlines the main challenges in implementing more effective approaches to visual object creation. It discusses the planning, implementation, control, optimization, and enhancement of existing approaches using artificial intelligence methods. The necessity of developing new methods for automated visual object construction in gamification tasks is established in this article. Furthermore, future research directions are proposed, including the simultaneous application of gamification and virtual reality technology to enhance user engagement, and learning outcomes. The paper concludes with the comparative analysis, research plans, and the potential outcomes of this study in terms of scientific novelty in the field of automated visual objects creation in gamification tasks.